PERAN ATURAN HUKUM DALAM MENJAGA KETERTIBAN MASYARAKAT - Ramadhan, Risqi Eka; Muzakki, Ilyyin Zabbar; Habibah, Siti Maizul (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Law is a rule that applies in society, whether it is a traditional society or a modern society. Naturally, peace and tranquility and order in life are achieved if society provides control, social supervision, both written and unwritten. Realistically, these elements of social control will undergo changes and developments both evolutionarily and revolutionarily in accordance with the development of society. Implementation of the regulation is a manifestation of the desire of the rule of law so that the function of social control and social control can be realized in society. Therefore, both law and society must adjust to each other's developments, so that there is harmony between the two.